Novel gallium(III) phthalocyanine derivatives - Synthesis, photophysics and photochemistry - Chauke, Vongani; Ogunsipe, Abimbola; Durmuş, Mahmut; Nyokong, Tebello (Pergamon-Elsevier Science Ltd, 2007)
The syntheses of gallium(III) chloride phthalocyanine {(CI)GaPc}, octaphenoxyplithalocyaninato gallium(III) chloride {(Cl)GaOPPc] and octakis(4-tert-butylphenoxy)phthalocyaninato gallium(III) chloride J(CI)GaOTBPPc); as well as their photophysical and photochemical parameters are hereby presented. Fluorescence quantum yields do not vary much among the three metallophthalocyanines (MPcs); therefore it was concluded that the effect of the substituents is not significant amongst (Cl)GaPc, (Cl)GaOPPc and (QGaOTBPPc. Solvents effects, however, had an effect on the results. Triplet quantum yields were found to be lower in DMSO than in DMF and toluene. The rate constants for fluorescence, intersystem crossing and internal conversion as well as fluorescence and triplet lifetimes are reported. We have also reported photodegradation and singlet oxygen quantum yields. There was no clear correlation between the later parameters. It was, however, established that the three MPcs were stable. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: gallium phthalocyanine; fluorescence; triplet quantum yield; triplet lifetime; singlet oxygen quantum yield; photostability